Prediction of Fracture Pattern in Defective Single Walled Carbon Nanotubes Using Molecular Structural Mechanics. (2016) - Patel, Ajay; Ardeshana, Bhavik; Jani, Umang; Joshi, Anand
Abstract: An atomistic-based dynamic crack model for recreating execution of carbon nanotubes by considering vacancy defects is projected. The idea of the fracture model is taking into account the supposition that carbon nanotubes, when stacked, carry on like space-casing structures. The finite element method is utilized to analyse the nanotube structure and the molecular structural mechanics approach with beam element is used to simulate the non-linear force field of the C–C bonds. The model has been applied to defected single walled chiral, arm chair and zigzag nanotubes subjected to critical tension. The defect presented here (model) is one absent atom at the centre of the nanotube. The anticipated crack advancement, failure stresses of the nanotubes correspond exceptionally well with sub-atomic mechanics model from the literature.